Recruitment of South Asians into asthma research: qualitative study of UK and US researchers - Stirland, Lucy (Prim Care Respir J, 2011)
BACKGROUND: There is increasing international concern about the persistent under-representation of ethnic minority patients in research. AIMS: We aimed to explore strategies being employed by US and UK researchers when attempting to recruit minority ethnic participants into research with a view to increasing participation by South Asians in UK asthma research. METHODS: Qualitative interviews with 36 asthma-interested researchers. RESULTS: Key themes were: the need to build long-term trusting relationships; ensuring that the procedures and practices used were respectful; paying attention to logistic considerations with respect to funding, the location of the research and taking proactive steps to overcome language-related barriers; and the importance of effective dissemination of results to, amongst others, the minority ethnic groups under study. The use of financial incentives or “co-payments” was reported as being a successfully-employed strategy in the US context, which could be considered for use in the UK. CONCLUSIONS: There is a need for funders and researchers to take proactive steps to develop longer-term relationships built on trust and respect with the populations they wish to study. Attention to the location of research, language considerations, financial reimbursement and appropriate dissemination of results are all likely to translate into improved recruitment of these “hard-to-reach” populations.